PENDIDIKAN BERKARAKTER PESERTA DIDIK SDN 10 TALANG UBI MELALUI PROGRAM IMTAQ - Parasih; Ega Rismasita; Siska Septia Ulfa; Leny Marlina; Febriyanti (Irfani (e-Journal), 2025)
ABSTRACT This study aims to analyze the role of the Faith and Piety Program (IMTAQ) in character building of students at SD Negeri 10 Talang Ubi. Using a qualitative descriptive method, this study collected data through literature studies, observations, interviews, and questionnaires. The survey results showed that the implementation of the IMTAQ Program contributed to improving students' discipline, responsibility, and social attitudes. However, there are challenges in implementing the program, such as limited facilities and infrastructure and the need to increase parental and community involvement. This study recommends increasing support for facilities, teacher training, and periodic evaluations to optimize the effectiveness of the program. Keywords: IMTAQ Program, character education, elementary school, moral development.